Neuronal Constituents and Putative Interactions Within the Drosophila Ellipsoid Body Neuropil - Omoto, Jaison Jiro; Nguyen, Bao-Chau Minh; Kandimalla, Pratyush; Lovick, Jennifer Kelly; Donlea, Jeffrey Michael; Hartenstein, Volker (Frontiers in Neural Circuits, 2018)
The central complex (CX) is a midline-situated collection of neuropil compartments in the arthropod central brain, implicated in higher-order processes such as goal-directed navigation. Here, we provide a systematic genetic-neuroanatomical analysis of the ellipsoid body (EB), a compartment which represents a major afferent portal of the Drosophila CX. The neuropil volume of the EB, along with its prominent input compartment, called the bulb, is subdivided into precisely tessellated domains, distinguishable based on intensity of the global marker DN-cadherin. EB tangential elements (so-called ring neurons), most of which are derived from the DALv2 neuroblast lineage, interconnect the bulb and EB domains in a topographically-organized fashion. Using the DN-cadherin domains as a framework, we first characterized the bulb-EB connectivity by Gal4 driver lines expressed in different DALv2 ring neuron (R-neuron) subclasses. We identified 11 subclasses, 6 of which correspond to previously described projection patterns, and 5 novel patterns. These subclasses both spatially (based on EB innervation pattern) and numerically (cell counts) summate to the total EB volume and R-neuron cell number, suggesting that our compilation of R-neuron subclasses approaches completion. EB columnar elements, as well as non-DALv2 derived extrinsic ring neurons (ExR-neurons), were also incorporated into this anatomical framework. Finally, we addressed the connectivity between R-neurons and their targets, using the anterograde trans-synaptic labeling method, trans-Tango. This study demonstrates putative interactions of R-neuron subclasses and reveals general principles of information flow within the EB network. Our work will facilitate the generation and testing of hypotheses regarding circuit interactions within the EB and the rest of the CX.